(untitled) (Texas Journal of Engineering and Technology, 2023)
The bearing capacity of the structure, determined by regulatory documents that limit the use of the plastic properties of the material, turns out to be underestimated. The current practice of optimal structural design (OPD) does not fully take into account the specific requirements (properties) for reinforced concrete structures. In this regard, research aimed at studying the assessment of the optimality and reliability of the structure both in the elastic and in the elastic-plastic stages of the material operation becomes relevant. Therefore, the authors attempt to assess the optimality and reliability of the design, taking into account a number of specific properties of reinforced concrete. In order to objectively assess the state of the structure in the elastic and elastic-plastic stages, a reliability assessment is carried out, which makes it possible to identify the possibilities of meeting the functional and operational requirements of the structure throughout the entire standard service life of the structure. As is customary in reliability theory, one of the main indicators for assessing reliability is the failure-free design, which takes into account the partial or complete loss of the functional properties of the system. The study proceeds from the fact that when solving optimization problems, a redistribution of efforts occurs due to a change (most often a decrease) in the parameters of the section of structural elements, which causes the elements to be predisposed to work in the elastic-plastic stage. The redistribution of forces leads to savings in materials, although inelastic deformations, the formation of cracks, and even partial decoupling of concrete with reinforcement, reduces the rigidity of structural elements. In order to study the design at the stages of both elastic and elastic-plastic, known methods and techniques are used